On applications of Little's formula. (1993) - Dshalalow Dshalalow, Jewgeni H. Jewgeni H.
Abstract : In classical Little's formula L = λ W used in queueing, the parameter λ serves as the intensity of the input process. In various applications this parameter may not be known. The author discusses important classes of modulated input processes, where this parameter can be found.